The Paris Agreement on Climate Change—Made in USA?. Issue 4 (December 2019) - Milkoreit, Manjana
Abstract : The 2015 Paris Agreement established a new logic for international climate governance: the pledge-and-review system. In 2009, the same idea had been proposed in the Copenhagen Accord, but was then forcefully rejected by the negotiation community. Explaining this turnaround, I analyze the role of the United States in the international climate negotiations, using Putnam's two-level game framework and Snidal's k-group theory. U.S. domestic politics imposed significant constraints on the terms of the Paris Agreement, contributing to the emergence of the new treaty architecture. Until 2015, U.S. negotiators were either unable or unwilling to bring the demands of political actors at the domestic and international levels in alignment. President Obama achieved this alignment in 2015 by creating international support for a treaty without legally binding obligations that could circumvent a Congressional ratification barrier. The latter required a surprising move: the proactive engagement of China despite the structural context of hegemonic transition.